INNOVATIVE INFORMATION TECHNOLOGIES IN THE MODERNIZATION OF BUSINESS INFORMATION SUPPORT (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Introduction. Expansion and improvement of the technology of electronic formation and transmission of accounting data requires a review of the key principles of information processing systems and accounting. Automation of the primary recording of accounting data using modern coding systems is of great importance in this regard.The purpose of the study is to determine the possibilities for the complex use of two-dimensional barcoding in the form of QR coding for business information provision, electronic data exchange, electronic documentation and document flow.Methods. The study uses historical and bibliographic methods, scientific abstraction, methods of comparative analysis, statistical and logical methods.Results. As part of the study the genesis of the introduction and development of barcoding technology and its use for information exchange has been studied. The expediency of using the technology of two-dimensional barcoding in the form of QR coding has been substantiated.Conclusions.The advantages and ways of using QR codes for business information support have been highlighted. New ways of applying barcoding for accounting purposes have been presented, in particular, for registering the movement of inventory, payment for goods, works, services, personnel management, access to information data on a website or other information resource, registration of relationships between business entities and exchanging documents.
Keywords: barcode marking, barcode, one-dimensional barcoding, two-dimensional barcoding, QR code, accounting, electronic documentation, electronic documents circulation.